Consumer experience of mental health services during the COVID-19 pandemic: Evidence from an Australian mental health system - Sarah Kelshaw; Jason Boyd; Irene Gallagher; Grant Sara (The Beryl Institute, 2022)
COVID-19 has increased the need for mental health care but disrupted its delivery. We examined impacts of the first year of the COVID-19 pandemic on consumer experience of NSW hospital and community mental health services, compared to their pre-COVID baseline. We also examined whether increased telehealth use was associated with changes in the quantity or experience of community mental health care. Data were 73,488 Your Experience of Service (YES) surveys from state mental health services in New South Wales (NSW), Australia, grouped into three periods: pre-COVID (January 2018 to March 2020), early-COVID (April to June 2020) and stable-COVID (July to December 2020). Experience scores were compared using mixed effects ordinal logistic regression. Supplementary questions on telehealth and community care (n=621) were examined by multinomial logistic regression. Experience scores improved significantly during the early-COVID period for community consumers and during the stable-COVID period for hospital consumers. Of community clients, 78% received some or all care by telehealth. Positive experience was more likely when most or all care was by telehealth and the amount of care increased. A reduced quantity of care, regardless of care modality, was the strongest predictor of worse experience. Increased service provision and telehealth support were well received over the first year of the pandemic. When contact hours are reduced due to COVID-19 risk mitigation strategies, it is vital to provide alternative methods of care such as telephone, or internet support, rather than just reducing face to face contact hours. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.